Prevention of Esophageal Damage During Ablation of Atrial Fibrillation by the Esophagus Mechanical Deviation - Mateos, Enrique Indalécio Pachón; Mateos, José Carlos Pachón Mateos; Amarante, Ricardo Carneiro; Pachón, Carlos Thiene Cunha; Lobo, Tasso Júlio; Peña, Tomás Guillermo Santillana; Acosta, Juán Carlos Zerpa; Mateos, Juán Carlos Pachón; Ortêncio, Felipe; Higuti, Christian (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Atrial fibrillation is the most prevalent arrhythmia in the world population. Despite the use of antiarrhythmics, it is difficult to control clinically, causing symptoms and mainly generating risk of a thromboembolic event. Since 1998, by means of radiofrequency ablation, the treatment of atrial fibrillation has completely changed, but together with this important evolution complications from this ablative treatment technique have also started. In addition to the pulmonary vein stenosis caused by the ablation and later corrected with the change in the technique, atrioesophageal fistulas appeared due to the application of radiofrequency in the posterior wall of the left atrium. This wall is very close (0.5 cm onaverage) to the esophagus, which facilitates the formation of the fistula that leads to the death of almost 100% of the affected patients, despite the various treatment measurements already developed. To avoid this serious complication, several authors have created techniques to protect the esophagus including its mechanical deviation to a region opposite to the radiofrequency application, taking advantage of its mobility and easiness of handling. The mechanical deviation of the esophagus has proven to be the simplest, cheapest and most efficient way to protect this organ from radiofrequency thermal damage during atrial fibrillation ablation.